REZIM PEMBANGUNAN INTERNASIONAL: DARI DISKURSUS HEGEMONIK HINGGA KEPENGATURAN POLITIK - Dewi Setiyaningsih (Review of International Relations, 2021)
Poverty and inequality has been being most concern problem for international community in decades. The idea to tackle these problems then created the development norm which becomes international development regime. This paper examines the problem of international development concept and how the conception is normally adopted by the developing countries as the main development model. It combines two critical aproach to analyze, postcolonial perspective developed by Gayatri Spivak and governmentality developed by Michele Foucault. Postcolonial perspective is used to analyze the problem of international development concept, while governmentality is used to analyse how the conception is adopted normally through the global political structure. It shows that the concept of international development defined by inter-governmental like UN (United Nations) contains hegemonic idea which is practiced normally through international institutions, governmental and non governmental organization. Keyword: international development, development regime, developmentalism.